The impact of intrapartum pethidine on the neonatal outcome: a perspective review - Husin, Roziah; Abdulwahab, Dalia F; BR, Rukaiah; Ismail, Rozihan (2012)
Objective: To study the effect of intrapartum pethidine administration on the fetal heart rate pattern and neonatal outcome. Method: This is a prospective observational study done on forty low risk uncomplicated pregnancy at term in the first stage of labour. The study was done in the labour suite in Hospital Tengku Ampuan Afzan Kuantan, Malaysia. Intramuscular Pethidine 1mg/kg was given as intrapartum analgesia to all consented patient with normal baseline fetal heart rate and clear liquor. Intrapartum fetal heart rate pattern and neonatal outcome were reviewed and analysed by SSPS 17.0. Results: Total of 40 patients recruited in this study with mean age of 27.9 ± 6.03 years and mean gestational age of 39.0 ± 0.81 weeks. The mean duration from pethidine administration to delivery is 285.5 ± 178.9 minutes (4 hours and 45 minutes). Out of 40 patients, 2 (5%) cases had suspicious CTG 1 hour post pethidine administration, first one with absence of acceleration and the second with early deceleration which lasted for 45 minutes and one hour respectively. All neonates delivered with good Apgar Score, 8 at 1 minute and 9 at 5 minute. A total of 9 (22.5%) cases were admitted to the Neonatal Intensive Care Unit (NICU). Seven (17.5%) cases were admitted for observation because of delivery less than 4 hours after pethidine administration, following the neonatal protocol at our centre. Two (5%) cases were admitted for G6PD. Neither required ventilation nor antidotes. All of them were discharged to mother after 24 hours apart from those admitted because of G6PD. Conclusion: Intrapartum pethidine is still an analgesic option which is simple, cheap and easily available without major effect to the fetal heart rate pattern and the neonatal outcome.